PSYCHOLOGICAL AND PEDAGOGICAL SUPPORT FOR STUDENTS UNDER CONDITIONS OF CHRONIC STRESS AND UNCERTAINTY IN THE EDUCATIONAL PROCESS - Жигло, Оксана (SWorldJournal, 2025)
The article is devoted to the analysis of psychological and pedagogical support for students in higher education institutions under conditions of chronic stress and uncertainty in the educational process. The focus of the study is a systemic approach to s